A MEDIATION ANALYSIS OF COGNITIVE AND AFFECTIVE CUSTOMER TRUST IN CUSTOMER LOYALTY TOWARDS E-MARKETPLACE - Hendriana, Evelyn; Anjani, Siti; Dennison, Alexander; Subhan, Zhafira Nur (Jurnal Aplikasi Manajemen, 2022)
Studies have shown the importance of customer trust in determining customer loyalty. While the psychological theory states that customer trust has cognitive and affective dimensions, earlier studies tended to look at it aggregately. An evaluation of the customer trust dimensions may provide a deeper understanding of the relative importance of each dimension of customer loyalty. This study looks at the roles of cognitive and affective customer trust in the context of the e-marketplace. As perceived privacy and security are still issues in the e-marketplace of developing countries, this study tries to examine the roles of cognitive and affective trust in mediating the relationships between perceived privacy, perceived security, corporate reputation, and customer loyalty. A close-ended questionnaire survey was distributed to answer the research questions. Data from 426 respondents were analyzed using PLS-SEM. The findings support the hypotheses of the interrelationship between the two dimensions of customer trust. This study also found that cognitive and affective trust mediates the relationships between corporate reputation, perceived security, and customer loyalty. However, we failed to prove the effect of perceived privacy on cognitive and affective trust.